Prevalence of contact allergy to p-phenylenediamine in the European general population - Diepgen, Thomas L.; Naldi, Luigi; Bruze, Magnus; Cazzaniga, Simone; Schuttelaar, Marie-Louise; Elsner, Peter; Goncalo, Margarida; Ofenloch, Robert; Svensson, Åke (The journal of investigative dermatology, 2016)
Population-based studies on contact allergy to p-phenylenediamine (PPD) are scarce. A cross-sectional study was performed to assess the prevalence of contact allergy to PPD and its risk factors in the general population of 5 European countries. A total of 10,425 subjects were interviewed, and a random sample (n = 2,739) was patch tested to PPD. Overall, 5,286 individuals (50.9%) reported having used hair colorants at least once in their lifetime (78% female, 20% male), and 35% had used hair colorants during the last 12 months. Hair colorant avoidance because of any skin problem during the lifetime was reported by 6%. Black henna tattoos had been used by 5.5% during their lifetime. The prevalence of PPD contact allergy was 0.8% (95% confidence interval 0.6-1.0%), with no statistically significant association with gender or hair dye use. The prevalence of PPD in black henna tattoo users was 3.2% versus 0.6% in nonusers (P < 0.001). A clinically relevant positive patch test reaction to PPD related to hair coloring products was found in 0.1% (95% confidence interval 0.0-0.2%). A significant association with PPD contact allergy was observed for subjects who had black henna tattoos in their lifetime, with an age- and gender-adjusted odds ratio of 9.33 (95% confidence interval 3.45-25.26, P < 0.001). Black henna tattoos are an important risk factor for PPD contact allergy.
Accepted 18 September 2015
Gesehen am 08.05.2020